Correlation between Lower Limb Power and Agility on Hand Grip Strength in three Different Positions in Young Fencers - Sarvaiya, Prachi H; Puntambekar, Anjali (International Journal of Innovative Research in Medical Science, 2022)
Background: Fencing is an open skilled combat sport, which requires grip strength, core strength and lower limb strength. Aim: To determine the correlation between lower limb power, agility and core on hand grip strength in three different positions - On-guard, Lunge and Defence in young fencers. Methodology: A correlational study was carried out on 23 young fencers in the age group of 14-25 years of age as per the inclusion and exclusion criteria. The outcome measures recorded were - The Standing Broad Jump test, 7-5-5-7 Agility test, Side Plank test - Right and Left, Hand grip strength in On-guard, Lunge and Defence. Results: It showed significant positive excellent correlation between lower limb power on hand grip strength in three different positions, significant negative moderate correlation between agility and hand grip strength in three different positions and significant positive moderate correlation between core stability and hand grip strength in three different positions. Conclusion: There is a significant correlation between lower limb power, agility and core on hand grip strength in three different positions in young fencers.